Peran Operator Wisata Bahari dan Wisatawan Terhadap Pelestarian Terumbu Karang di Pulau Menjangan Kawasan Taman Nasional Bali Barat - Wahyuni, Ida Ayu Tri; Adikampana, I Made (JURNAL DESTINASI PARIWISATA; Vol 9 No 1 (2021): VOL 9, NO 1 (2021): (JANUARY-JUNE) JURNAL DESTINASI PARIWISATA, 2021)
Menjangan Island is a small island located 5 miles northwest of the island of Bali and is part of the West Bali National Park area. Activities that can be carried out by tourists visiting Menjangan Island, namely diving, snorkeling, jungle tracking, walking around Menjangan Island. The condition and condition of good coral reefs on Menjangan Island is certainly inseparable from the role of a person or group in preserving and conserving coral reefs in this island. This study aims to determine how the role of Marine and Tourist Tourism Operators on coral reef preservation on Menjangan Island.This research used a qualitative method with qualitative data analysis techniques. Sources of data from this study come from primary data and secondary data. The results of this study indicate that marine tourism operators and tourists are very instrumental in preserving coral reefs on Menjangan Island because it can be seen from the efforts made to maintain the beauty of the underwater world on Menjangan Island. The form of preservation carried out in the form of providing education to tourists related to how to do snorkeling and diving activities so as not to damage the coral reefs. Keyword: Roles, Marine Tourism Operators, Tourist, Coral Reef Conservation, Menjangan Island